ECONOMIC FISH LANDED AT THE NUSANTARA FISHERY PORT (PPN) AWANG BAY - Lestari, Rizky Ayu; Supenti, Lilis; Sari, Heny Budi Purnama; Azis, Muh Aksa (Universitas Mataram, 2025)
Shrimp is one of the important export commodities from the Indonesian fishery sector due to the considerable contribution to the economy. Rendemen on frozen shrimp processing can affect the financial aspect of the company. The purpose of this research is to know the flow of frozen shrimp processing, shrimp soaked with different time and size, and the quality of the raw material and the final product. Frozen raw shrimp processing process includes Raw Material Acceptance, Washing I, Weighing I, Cutting Head, Washing II, Weighing II, Initial Sorting, Final Sorting, Weighing III, Peeling and Intestinal Disposal, Washing III, Weighing IV, soaked, Weighing V, Laundering IV, Preparation, Freezing, VI Weighing, Glazing, Packaging, Metal Detection, Flap and Storage. shrimp soaked with different time and size obtained by different increase result for size 41/50 has a small increase percentage compared to size 61/70 and 71/90 which have big increase. The quality of peeled and deveined peeled shrimp products based on organoleptic test of fresh shrimp and finished product has met the standard. The quality of sensory shrimp raw shrimp PND with size 41/50, 61/70, 71/90 with soaked time of 2 and 4 hours still received by panelists based on the parameters of appearance, odor, taste and texture. Shrimp quality based on microbiology (ALT, E. coli, Salmonella, and V.chollerae) and chemistry (antibiotics) have met the standard.